Light‐Emitting Diodes: Light‐Emitting Diodes with Hierarchical and Multifunctional Surface Structures for High Light Extraction and an Antifouling Effect (Small 2/2016). Issue 2 (January 2016) - Leem, Young‐Chul; Park, Jung Su; Kim, Joon Heon; Myoung, NoSoung; Yim, Sang‐Youp; Jeong, Sehee; Lim, Wantae; Kim, Sung‐Tae; Park, Seong‐Ju
Abstract : Bioinspired hierarchical structures on the surface of vertical light‐emitting diodes (VLEDs) are fabricated by S.‐J. Park and co‐workers based on combining a self‐assembled dip‐coating process and nanopatterning transfer method using thermal release tape. These novel surfaces reduce the total internal reflection and grant additional antifouling abilities to VLEDs. On page 161, this provides a guideline for the design of various optoelectronic devices where not only high performance but also considerably reduced contamination by the environment are required for efficient LEDs with long operational lifespans.